2016
DOI: 10.1002/bjs.9958
|View full text |Cite
|
Sign up to set email alerts
|

Volume–outcome relationship in pancreatic surgery

Abstract: Although mortality related to pancreatic surgery is influenced by many factors, this study demonstrated lower mortality at 1 year in high-volume centres in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 26 publications
3
42
0
10
Order By: Relevance
“…Similar results have been demonstrated in a recent study on pancreatic surgery with 10,000 AOK (German common health insurance) patients who were operated in 683 hospitals. In the institutions which had performed only eleven such interventions in 3 years, mortality during the first year after surgery was 50% higher than in the quintile with the most operations (34.4 vs. 23.3%) [20].…”
Section: Surgical Oncologymentioning
confidence: 84%
“…Similar results have been demonstrated in a recent study on pancreatic surgery with 10,000 AOK (German common health insurance) patients who were operated in 683 hospitals. In the institutions which had performed only eleven such interventions in 3 years, mortality during the first year after surgery was 50% higher than in the quintile with the most operations (34.4 vs. 23.3%) [20].…”
Section: Surgical Oncologymentioning
confidence: 84%
“…After screening of titles and abstracts, 51 articles were excluded and of the remaining 6, 4 publications were suitable for inclusion in the present study [9,[11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…This study found a mild trend towards a concentration of care structures within the field of pancreatic surgery from 2005 through 2011 (percentage of hospitals with caseload below minimum caseload requirements: 64.1 to 48.7%; percentage of pancreatic surgery cases in hospitals below minimum caseload requirements: 19.4 to 11.4%, respectively), which seemed to stop between 2011 and 2013 [9]. Another study assessed volume-outcome relationships related to pancreatic surgery using hospital discharge data from Germany's largest provider of statutory health insurance [13]. Although this provider covers only 30% of Germany's population, its database offers the possibility to follow up patients for up to 1 year beyond the initial inpatient episode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to current routine data, however, the overall mortality in Germany is approximately 10% [8,14]. The recently conducted multicenter randomized trial RECOPANC on pancreatoduodenectomy also showed a mortality of just over 5%, although participants were academic high-volume centers for pancreatic surgery [15].…”
Section: Reference Values For Perioperative Mortalitymentioning
confidence: 99%